The Effect of small producer organization strengthening project on women's empowerment - KIM, Daehwan (KDI School, 2023)
Despite the 2030 Agenda for Sustainable Development, the gender inequality and disempowerment of women persist around the world. Considering the vulnerability and poverty situation of rural women, the study evaluated the effect of the small rural producer organization strengthening project on women’s empowerment in Paraguay. Due to the data constraints, a simple before-and-after quantitative design was mixed with a post-only nonequivalent comparison qualitative design. The case study shows that (1) little or no effect on the role division between men and women in the households, (2) significant time reduction of women in people care and garden work at the same time with a significant household income increase, (3) no effect on decision-making by gender, (4) the greatest effect on the women’s participation, (5) perception difference on violence against women between men and women but greater consensus on the prevention and intervention about violence in the project beneficiary group. In conclusion, we observed the greater participation of women in producer organization and their income increase. But it did not change the gender role in the households nor decision-making role. In addition, it has confirmed the economic disparity between men and women producers. Finally, it is important to mention that the research has limitations to demonstrate that the project interventions alone caused those changes.
Thesis(Master) -- KDI School: Master of Devemopment Policy, 2023
Keywords: Women--Economic conditions--Paraguay; Women in economic development--Paraguay